2008
DOI: 10.1007/s11046-008-9127-y
|View full text |Cite
|
Sign up to set email alerts
|

PCR Analysis of the Tri13 gene to Determine the Genetic Potential of Fusarium graminearum Isolates from Iran to Produce Nivalenol and Deoxynivalenol

Abstract: Fusarium graminearum trichothecene producing isolates can be broadly divided into two chemotypes based on the production of the 8- ketotrichothecenes deoxynivalenol (DON) and nivalenol (NIV). Functional Tri13 gene required for the production of NIV and 4- acetyl NIV, whereas in the isolates producing DON and its acetylated derivates, this gene is nonfunctional. In this study, a total of 57 isolates from different fields of Mazandaran province, Iran were identified as F. graminearum using classical methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
4
21
0
Order By: Relevance
“…These markers have also provided knowledge about nucleotide sequence homology and orthologous genes among genomes (Nicholson et al, 1998;Adinolfi et al, 2007;Saharan et al, 2007). They are frequently used in the molecular characterization of Fusarium at the genus and species levels (Schilling et al, 1996;Haratian et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These markers have also provided knowledge about nucleotide sequence homology and orthologous genes among genomes (Nicholson et al, 1998;Adinolfi et al, 2007;Saharan et al, 2007). They are frequently used in the molecular characterization of Fusarium at the genus and species levels (Schilling et al, 1996;Haratian et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their carcinogenic effects, they inhibit ribosomal protein synthesis (Gutleb et al, 2002). Research has recently focused on the molecular characterization of causal agents and the production of mycotoxins to improve pathogen recognition (Saharan et al, 2007;Haratian et al, 2008;Pandolfi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Such a wide F. poae occurrence is unfavorable, as this species belongs to the causal agents of Fusarium ear rot (Chełkowski et al 2007), which is one of the most important maize diseasesdecreasing yield and affecting grain quality and feed value of the grain (Czembor et al 2010;Rahjoo et al 2008). Haratian et al (2008) applied the positive-negative PCR assay based on the Tri13 gene to identify the genetic potential of DON and NIV production of F. graminearum. In this study, only 11 Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In other species detected by these authors, the NIV chemotype was also sporadically detected (representing only 5.8% of the total population). Haratian et al (2008) revealed that both DON and NIV Fusarium spp. chemotypes existed in Iran, but NIV producers were more frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…For chemotype identification, there is a rapid procedure based on the amplification of specific genes encoding for proteins involved in mycotoxin biosynthesis. Genes such as: TRI2, TRI3, TRI5, TRI6, TRI7, TRI13 and TRI101 are encoded for biosynthesis of trichothecene and can be assayed by PCR to identify the ability of trichothecene biosynthesis and also chemotypes of the fungi (Chandler et al 2003;Haratian et al 2008;Sampietro et al 2010;Yoruk et al 2016).…”
Section: Introductionmentioning
confidence: 99%